The causes and prevention of cancer. - Ames, B N (1995)
Epidemiological evidence indicates that avoidance of smoking, increased consumption of fruits and vegetables, and control of infections will have a major effect on reducing rates of cancer. Other factors include avoidance of intense sun exposure, increases in physical activity, and reduction of alcohol consumption and possibly red meat. A substantial reduction in breast cancer is likely to require modification of sex hormone levels, and development of practical methods for doing so is a high research priority. Resolution of the potential protective roles of specific antioxidants and other constituents of fruits and vegetables deserves major attention. Mechanistic studies of carcinogenesis indicate an important role of endogenous oxidative damage to DNA that is balanced by elaborate defense and repair processes. Also key is the rate of cell division, which is influenced by hormones, growth, cytotoxicity, and inflammation, as this determines the probability of converting DNA lesions to mutations. These mechanisms may underlie many epidemiologic observations.